2022
DOI: 10.2166/nh.2022.003
|View full text |Cite
|
Sign up to set email alerts
|

How do we identify flash droughts? A case study in Central European Croplands

Abstract: Many definitions and delineation methods exist for identifying flash droughts (FDs), which are events of rapid and unusual large depletion of root-zone soil moisture, in comparison to average moisture conditions, due to climatic compound conditions over a short period of several weeks. Six FD identification methods were compared to analyse their functioning using data from several experimental cropland sites across Central Europe. Co- and misidentification of the FD time series were assessed using confusion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…Noguera et al (2021) demonstrated that using different variables, even while employing the same identification methodology, can reveal very different results regarding the spatial and seasonal hotspots of flash drought within Spain. Alencar and Paton (2022) used time series analysis to show how various methods and indicators result in substantial variability in flash drought timing and intensity.…”
Section: Flash Drought Climatological Characteristicsmentioning
confidence: 99%
“…Noguera et al (2021) demonstrated that using different variables, even while employing the same identification methodology, can reveal very different results regarding the spatial and seasonal hotspots of flash drought within Spain. Alencar and Paton (2022) used time series analysis to show how various methods and indicators result in substantial variability in flash drought timing and intensity.…”
Section: Flash Drought Climatological Characteristicsmentioning
confidence: 99%
“…We further calculated empirical yield gaps per county for 12 crops for the last 10 years (2013)(2014)(2015)(2016)(2017)(2018)(2019)(2020)(2021)(2022), by subtracting actual reported yields (total production in tonnes) by the regional statistical authority (Amt für Statistik Berlin-Brandenburg, 2022;Alencar, 2022) from an estimate of expected yields under non-drought conditions. We refer to expected yields as the product of cropped area (per crop type in a given year) and the respective 5-year average yield (tonnes per hectare) per LBG from the time 2010-2014.…”
Section: Impact Indicators: Crop Health Observations and Empirical Yi...mentioning
confidence: 99%
“…Rapid onset is a decisive factor in the definition FDs. Multiple conflicting definitions have been proposed since its introduction in the academic literature (Alencar and Paton 2022). An initial debate focused on whether FDs were short-lived droughts (Mo and Lettenmaier 2016), or intense evolving droughts (Ford and Labosier 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, seminal questions remain concerning what should be considered an FD. Although clear thresholds have been proposed (Christian, Basara, Otkin, et al 2019;Li et al 2020;Osman et al 2021;Yuan et al 2023), their transferability across case studies is limited (Alencar and Paton 2022). The lack of wellestablished criteria has led to a growing diversity of definitions and monitoring tools for FDs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation